Is HPV the Novel Target in Male Idiopathic Infertility? A Systematic Review of the Literature - Muscianisi, Francesco; De Toni, Luca; Giorato, Gloria; Carosso, Andrea; Foresta, Carlo; Garolla, Andrea (Frontiers in Endocrinology, 2021)
Infertility is an important health problem that affects up to 16% of couples worldwide. Male infertility is responsible for about 50% of the cases, and the various causes of male infertility may be classified in pre-testicular (for example hypothalamic diseases), testicular and post-testicular (for example obstructive pathologies of seminal ducts) causes. Sexually transmitted infections (STI) are increasingly widely accepted by researchers and clinicians as aetiological factors of male infertility. In particular, several recent reports have documented the presence of HPV in seminal fluid and observed that sperm infection can also be present in sexually active asymptomatic male and infertile patients. In this review, we aimed to perform a systematic review of the whole body of literature exploring the impact of HPV infection in natural and assisted fertility outcomes, from both an experimental and a clinical point of view. Starting from in-vitro studies in animals up to in-vivo studies in humans, we aimed to study and evaluate the weight of this infection as a possible cause of idiopathic infertility in males with any known cause of conception failure.